Special features of contemporary scenic speech education of students with “puppet artist” specialty (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2019)
The article presents the rationale that training for scenic speech for puppeteers should be specific, that is, differ in their structure, composition due to its focus on overcoming the physical obstacles of the actor puppeteer in contemporary theater.